Membangun Generasi Muda Toleran: Penguatan Moderasi Beragama di Desa Multi Agama - Bule, Yosep Aurelius Woi; Suswakara, Ignasius (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
This community service activity explores the practice of religious moderation in Nanganesa Village, focusing on young people. Observation of the problem is pointed by the increasing activity of youth religious organizations but the lack of relations and interactions between organizations and young people of different religions in Nanganesa Village. The service was conducted using a Community-Based Participatory Research (CBPR) approach to examine religious moderation practices in the village. Through questionnaires and focus group discussions (FGD), the team identified strengths, weaknesses, opportunities, and threats in fostering religious moderation at the local level. The study results indicate that strong social bonds, environmental support, and the active role of religious leaders are factors that promote tolerance. Nonetheless, the influence of social media and the lack of interfaith activities pose challenges that need to be addressed. The socialization of religious moderation aims to strengthen bonds of tolerance among youth of different faiths and their ability to resist extreme and radical ideologies in religion. This community engagement activity should be continued with follow-up efforts, such as strengthening tolerance education, media and technology literacy for young people through their respective religious organizations and increasing cross-organizational activities that can accommodate young people from various religions to strengthen religious moderation among young people.